Synthesis of Peripherally Tetrasubstituted Phthalocyanines and Their Applications in Schottky Barrier Diodes - Semih Gorduk; Ozge Koyun; Oguzhan Avciata; Ahmet Altindal; Ulvi Avciata (Journal of Chemistry)
New metal-free and metallophthalocyanine compounds (Zn, Co, Ni, and Cu) were synthesized using 2-hydroxymethyl-1,4-benzodioxan and 4-nitrophthalonitrile compounds. All newly synthesized compounds were characterized by elemental analysis, FT-IR, UV-Vis, 1H-NMR, MALDI-TOF MS, and GC-MS techniques. The applications of synthesized compounds in Schottky barrier diodes were investigated. Ag/Pc/p–Si structures were fabricated and charge transport mechanism in these devices was investigated using dc technique. It was observed from the analysis of the experimental results that the charge transport can be described by Ohmic conduction at low values of the reverse bias. On the other hand, the voltage dependence of the measured current for high values of the applied reverse bias indicated that space charge limited conduction is the dominant mechanism responsible for dc conduction. From the observed voltage dependence of the current density under forward bias conditions, it has been concluded that the charge transport is dominated by Poole-Frenkel emission.